SERAPAN KOSAKATA BAHASA ARAB MEMPENGARUHI BUDAYA ISLAM BATAK ANGKOLA-MANDAILING - Husniah Ramadhani Pulungan (Universitas Muhammadiyah Tapanuli Selatan, 2016)
Islamic culture of Batak Angkola Mandailing (BAM) is influenced by vocabulary absorption of Arabic Language. History has mentioned that Arabic language brought by Arabic, Gujarat and Persian merchant in order to spread Islam. The vocabulary absorption of Arabic language has happened because there is no match vocabulary or word in BAM and to help the society to communicate and avoid the misunderstanding among them. Moreover, the society of BAM used it actively and becomes the part of their culture in daily communication